The Influence of Facilities, Service Quality and Price Perceptions on Trans Batam Bus Passenger Satisfaction - Harlan, Fandy Bestario; Rahman, Fuad Arif; Gultom, Josua Partogi Tua Haholongan (Journal of Applied Business Administration, 2024)
Transportation is something that is very close and cannot be separated in today's life. Facilities are elements related to the level of satisfaction of service users. The availability of adequate facilities encourages passengers to feel satisfaction with the company's performance. The research uses quantitative analysis methods. The aim of this research is to determine the significant influence of facilities, service quality and price perceptions partially and simultaneously on Trans Batam user satisfaction. This research found that partially facilities (X1), service quality (X2) and price perception (X3) had a significant influence on passenger satisfaction (Y). From the test results, the calculated F value is 155,889 with the F table being 2.65 so that the calculated F value > F table or 155,889 > 2.65 and the significant level is 0.000 < 0.05, so H4 is accepted, it can be concluded that simultaneously the facility variables (X1), service quality (X2) and price perception (X3) simultaneously influence Trans Batam Bus passenger satisfaction.